IMPACTS OF PSYCHOLOGICAL DISORDER ON KIDS. - Anjali Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
For a child to be considered mentally healthy, they must be able to deal with stress in any given circumstance, participate in activities at school, at home, and in the community without experiencing negative emotions such as rage, anxiety, or depression (Mental Health Foundation, n.d.). A sound mental state during one's formative years is essential to a child's overall growth as well as to realising one's own full potential as an adult. Changes or traumatic experiences that occur in the life of a kid are frequently what sets off the development of mental disorders rather than the diseases developing on their own.